Can the WTO appellate Body Apply the Domestic Jurisdictional Rules? - Abd Almohsen Alajmy (Journal of Educational and Human Sciences, 2022)
The number of Regional Trade Agreements (RTAs) between countries has significantly increased over the past few decades. RTA may include rights and obligations that are parallel to those of WTO agreement, and provide for its own dispute settlement mechanism that is different from WTO Dispute Settlement Understanding (DSU). This forum clause allows parties to both RTA and WTO to litigate their dispute outside the DSU. This article addresses the issue of jurisdictional conflict between the RTAs and the WTO dispute mechanism over a claim that is violative of both WTO and RTA’s obligations.The main question this article answers is whether it is possible for the forum clause incorporated in RTA to divest the jurisdiction of WTO if invoked during the proceeding. This article analyzes a number of cases and RTAs involving a choice of forum clause before the WTO panel. This paper proceeds to examine different legal principles to find a legal justification to reconcile the jurisdictional scope of both RTA and WTO. As in current international legal principles do not offer an effective solution, this paper suggests that DSU should be amended to provide a set of rules governing the conflict between the RTA and WTO jurisdictions.